The role of economists in on-farm testing in agricultural research - Lynam, John K.; Sanders, J.H. (International Center for Tropical Agriculture, 1980)
Agricultural research in developing countries has lacked relevance to farm-level production problems, especially appropriate technologies for small-scale or limited-resource farmers. Currently research institutions are directing their efforts towards these objectives. This paper is a preliminary assessment of the research carried out by international and national centers, especially the regional trials conducted by CIAT, emphasizing their economical aspects. The strategy developed by the CIAT Cassava Program to increase crop productivity by a min-input technological package is described in detail. It is concluded that economic analysis is a critical component in the process of on-farm research, especially in ex-ante evaluations on technology adoption. (Extracted from CIAT)